Автоматизация проектирования строительных и технических объектов - Аветисян Д. А. Джон Амаякович; Игнатов В. П. Валентин Павлович; Фролов Г. Д. Геннадий Дмитриевич; Эпельцвейг Г. Я. Гарри Яковлевич; Криницкий Н. А. Николай Андреевич (Москва, Наука, 1986)
Исключено из фонда НТБ ТПУ